Metabolic Systemic Effects Triiodothyronine - E. A. Troshina; E. S. Senyushkina (SINAPS LLC, 2020)
Triiodothyronine (T3, 3,5,3'-L-triiodothyronine) is a thyroid hormone (thyroid), the secretion of which is carried out directly both by the gland (to a lesser extent) and outside it (the main amount; as a result of peripheral deiodination of thyroxine (T4)). Getting into the nuclei of cells, T3 interacts with specific nuclear receptors of target tissues, which determines its biological activity. This interaction leads to the activation of transcription of a number of genes.In the pituitary gland and peripheral tissues, the action of thyroid hormones is modulated by local deiodinases, which convert T4 to more active T3, the molecular effects of which in individual tissues depend on subtypes of T3 receptors and their interaction with other ligands, coactivators and corepressors, as well as on the activation or repression of specific genes.The reason for the lack of T3 production is primarily a deficiency of iodine in the diet, less often, a defect in the genes encoding the proteins that are involved in T3 biosynthesis. As a result of the low intake of iodide in the body, the so-called adaptive mechanism is activated, which consists in increasing the proportion of synthesized T3, which increases the metabolic efficiency of thyroid homones. With a deficiency in the diet of such a trace element as selenium, the conversion of T4 to T3 is reduced.Thyroid hormones play a vital role in the regulation of homeostasis and the metabolic rate of cells and tissues of humans and mammals. They are necessary for physical and mental development. Their insufficient production at the stage of formation of the internal organs of the fetus and in childhood can lead to various pathologies, primarily to pathology of the central nervous system, and as a result, growth retardation and mental retardation. In adulthood, hypothyroidism leads to a decrease in metabolism, memory impairment, depressive disorders, impaired fertility. Many discussions and ambiguous conclusions have been obtained regarding combination drugs (sodium levothyroxine + lyothironon) for the treatment of hypothyroidism. This article will examine the metabolic effects of T3, the thyroid hormone with the highest activity.